2008
DOI: 10.1071/rd07152
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial modifications during early pregnancy in bonnet monkeys (Macaca radiata)

Abstract: The present study was undertaken to investigate endometrial modifications that occur before embryo invasion in bonnet monkeys (Macaca radiata). These changes were analysed in luminal epithelium, glandular epithelium and stroma of endometrial functionalis on Day 6 post ovulation from pregnant and non-pregnant animals (n = 4 each) by transmission electron microscopy. Distinct features (i.e. loss of columnar shape by epithelial cells, changes in mitochondrial size and diffused apicolateral gap junctions) were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 62 publications
1
17
0
1
Order By: Relevance
“…Therefore, this alternate pathway may become functional during the early stages of decidualization in which stromal cells undergo a wave of proliferation. In accordance, we have observed an increase in stromal cell proliferation during early pregnancy in bonnet monkeys [24]. The present study revealed that pregnant bonnet monkeys had higher expression of PTGS2 in endometrial stroma.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, this alternate pathway may become functional during the early stages of decidualization in which stromal cells undergo a wave of proliferation. In accordance, we have observed an increase in stromal cell proliferation during early pregnancy in bonnet monkeys [24]. The present study revealed that pregnant bonnet monkeys had higher expression of PTGS2 in endometrial stroma.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous investigations demonstrated altered expression of estrogen-responsive genes such as estrogen receptor alpha in bonnet monkey endometrium during early pregnancy [24]. This is in contrast to sheep, in which loss of estrogen receptor alpha was observed during the periimplantation period [17].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…mtDNA copy number is a measure of mitochondrial biogenesis. Increased numbers of mitochondria and increased mitochondrial size were observed in the glandular epithelium and stromal endometrium of pregnant bonnet monkeys, an effect attributed to increased E 2 [Rosario et al, 2008]. We reported that E 2 significantly increased mtDNA copy number after 24, 48, and 72 h. in MCF-7 cells [Mattingly et al, 2008].…”
Section: Effect Of Estrogens On Mitochondrial Biogenesismentioning
confidence: 99%